PELATIHAN PENGUJIAN ASPAL UNTUK PEMELIHARAAN JALAN PEDESAAN BERDASARKAN SPESIFIKASI ASPAL PEN 60/70 DENGAN VIRTUAL ANALYSIS - Juang Akbardin; Kyki Bagas Styadi; Fia Nur Azizah (Lentera Karya Edukasi, 2022)
Abstract: The high increase in rural road construction requires standard achievements in accordance with the specifications specified in the implementation of road construction work. The limited resources for technicians in rural areas often result in non-achievement of road infrastructure specification standards being implemented. Asphalt testing training for rural road maintenance has the aim of increasing the knowledge capacity of the workforce in the implementation of road construction to obtain results that are in accordance with the standards and specifications set in rural road maintenance work. The training method used is virtual analysis and an approach to active participation by the community to gain asphalt testing knowledge in accordance with established national standards. The implementation of the training involves stakeholders in the community for implementing rural road construction Abstrak: Peningkatan pembangunan jalan pedesaan yang tinggi memerlukan capaian standart sesuai dengan spesifikasi yang ditentukan dalam pelaksanaan pekerjaan konstruksi jalan. Sumber daya tenaga teknisi yang terbatas dipedesaan seringkali menyebabkan tidak tercapainya standar spesifikasi infrstruktur jalan yang dilaksanakan. Pelatihan pengujian aspal untuk pemeliharaan jalan pedesaan mempunyai tujuan meningkatkan kapasitas pengetahuan tenaga kerja pada pelaksaaan pembangunan jalan untuk mendapatkan capaian hasil yang sesuai dengan standart dan spesifikasi yang ditetapkan dalam pekerjaan pemeliharaan jalan dipedesaan. Metode pelatihan yang digunakan merupakan virtual analisis dan pendekataan partisipasi aktif masyarakat untuk mendapatkan pengetahuan pengujian aspal sesuai dengan standart nasional yang ditetapkan. Pelaksanaan pelatihan melibatkan stakeholder pada masyarakat penyelenggaraan  pembangunan jalan dipedesaan